PLANT PHARMACOGNOSY FOR DENGUE FEVER: BACK TO NATURE - Bunawan, Hamidun; Baharum, Syarul Nataqain (Asian Journal of Pharmaceutical and Clinical Research, 2015)
No abstract needeed - Letter to the Editor